Evaluation of Dietary Electrolyte Balance on Nursery Pig Performance - A. Jones; J. C. Woodworth; S. S. Dritz; M. D. Tokach; J. M. DeRouchey; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2016)
A total of 2,880 pigs (PIC 327 × L42; initial BW 11.4 lb) were used in a 35-d growth performance trial evaluating the effects of dietary electrolyte balance (dEB) on growth performance of nursery pigs. There were 30 pigs per pen (60 pigs per double-sided feeder) and 12 replications (feeder) per treatment. Pens of pigs were allotted by BW and sex on arrival, and randomly assigned to 1 of 4 dietary treatments. Treatment diets were corn-soybean meal-based with dried whey and other specialty protein sources used in Phase 1 with decreased amounts in Phase 2. Dietary electrolyte balance was determined using the following equation: dEB = ((Na*434.98) + (K*255.74) – (Cl*282.06)) mEq/ kg. Phase 1 diets had dEB’s of 84, 137, 190, and 243 mEq/kg. Phase 2 diets had dEB’s of 29, 86, 143, and 199 mEq/kg. Limestone was used as the main Ca source in the high dEB diet and was replaced by increasing levels of CaCl2to form the other experimental diets. The lowest dEB diets were achieved by adding 1.17% and 1.25% CaCl2in Phase 1 and Phase 2, respectively. The highest dEB diets required additions of 0.55 and 0.80% limestone for Phases 1 and 2, respectively. The two intermediate diets were then balanced to have an equal stepwise increase in dEB. Dietary Ca concentrations were maintained in the three highest dEB diets, but increased in the low dEB diet with the increasing level of CaCl2. After d 21 of experimental diets, a common Phase 3 diet (Table 3) was fed to all pigs and was a typical nursery diet fed in commercial production with a dEB of 257 mEq/kg. From d 0 to 8 (Phase 1), decreasing dEB decreased (quadratic, P<0.05) ADG, ADFI, and final BW, and worsened (quadratic, P = 0.042) F/G. Likewise, from d 8 to 21 (Phase 2), ADG (quadratic, P = 0.022) and ADFI (linear, P = 0.011) decreased as dEB was decreased, resulting in a worsening of feed efficiency (quadratic, P<0.001). From d 0 to 21, ADG and ADFI decreased (linear, P<0.05) as dEB decreased resulting in poorer (quadratic, P<0.001) F/G. When a common diet was fed from d 21 to 35 (Phase 3), pigs that were previously fed low dEB diets had improved (linear, P<0.001) ADG and F/G; however, no differences were observed for feed intake. Overall (d 0 to 35), decreasing dEB in nursery diets from d 0 to 21 caused a reduction in ADG and final BW (linear, P<0.001), which was the result of a tendency for lower ADFI (linear P = 0.077) and poorer feed efficiency (quadratic, P = 0.028). In conclusion, feeding reducing levels of dietary dEB in nursery diets resulted in poorer growth performance of weanling pigs.
Keywords: dietary electrolyte balance; growth performance; nursery pig